ANALYSIS OF FLYPAPER EFFECT REVENUE SHARING FUND (DBH) AND REGIONALLY GENERATED REVENUE (PAD) TOWARD CAPITAL EXPENDITURE BY DISTRICT / TOWN IN SOUTH SUMATERA 2009-2011 - Marliana .; Mukhtaruddin .; Ika Sasti Ferina (AKUNTABILITAS, 2012)
This research aims to identify the influence of Flypaper Effect Revenue Sharing Fund (DBH) and Regionally Generated Revenue (PAD) toward capital expenditure by District / Town in South Sumatra 2009-2011. The population in this research was all of District / Town in South Sumatera in 2009 until 2011 and can be accessed at www.djpk.depkeu.go.id Site. Total Sample in this research is 15 districts /towns which consist of 11 districts and 4 towns in South Sumatera. Data were analyzed with tests of classic assumption and examination of hypothesis with multiple linear regression method. Based on the F test results indicate that the DBH and the PAD have influence on capital expenditure. Then through t test shows that DBH showed an influence on the probability of capital expenditure under the = 5% (0.000). While the PAD has no effect on the profitability of capital expenditure above = 5% (0.60). From the results of this study also demonstrated the occurrence of flypaper in districts / towns in South Sumatera, but had no flypaper effect against capital expenditure forecast. Â  Keywords: Capital Expenditure, Revenue Sharing Fund, Flypaper Effect, Regionally Generated Revenue